(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Construction industries are known to be hazardous due to complex tasks, change of work location, climatic conditions and temporary organizational management. The consequences of these hazards may involve occupational diseases, injuries and fatality. Injuries and accident rates are high in a construction site when compared with other manufacturing industries. Safety is one of the key factors in construction sites to mitigate the severity of the risk. Assessing the performance of the site concerning safety is an important part of the management system as it provides information on the safety of the worker as well as the task. Hence the aim of this research is to investigate the site safety performance and propose a methodology for enhancement. This is done in basically four parts viz., quantification of risk involved in each task, accounting for unsafe supervision, selection of right worker for the right task and usage e.g., PPEs. Safety performance cannot be measured only with the accidents/injuries in the site but the factors which influence the unplanned events have to be highlighted while determining the performance rate. The factors include the task/conditions of the site. Risk involved in each task is quantified using Hazard Identification and Risk Assessment (HIRA) technique. The hazards in the sites are identified through direct observation and previous safety reports and the risk values are determined using likelihood and severity ratings of each hazard. It is known that the construction site has 13.3% of low risk, 37.7 % of medium risk, 44.4 % of high risk and 4.6 % of extreme risk. The relative percentage of risk involved in each task is calculated and it is found that crane operation (10.4%), height work (9.1%) and drilling (8.8%) are the three major tasks with high risk. It is observed that in the particular construction site the relative percentage of low risk is very less. Furthermore, it can be said that by task-based risk quantification the builders/owners may look for suitable or alternate control measures to reduce the risk level to as low as reasonably practicable. This will automatically improve the performance of the site.